2017
DOI: 10.1016/j.cell.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Infiltrating T Cells in Liver Cancer Revealed by Single-Cell Sequencing

Abstract: Systematic interrogation of tumor-infiltrating lymphocytes is key to the development of immunotherapies and the prediction of their clinical responses in cancers. Here, we perform deep single-cell RNA sequencing on 5,063 single T cells isolated from peripheral blood, tumor, and adjacent normal tissues from six hepatocellular carcinoma patients. The transcriptional profiles of these individual cells, coupled with assembled T cell receptor (TCR) sequences, enable us to identify 11 T cell subsets based on their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

116
1,671
6
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,700 publications
(1,798 citation statements)
references
References 52 publications
116
1,671
6
5
Order By: Relevance
“…Others have also shown that T RM numbers are increased in livers with chronic HBV infection compared with healthy livers 31. Recent large-scale single-cell RNA-sequencing on T cells from a majority of HBV-related HCCs also found that T REG and exhausted CD8 + T cells (with similar gene signatures as our current study) were enriched in the tumour 32. The important roles of NK cells in HBV infection and HCC have been widely described 33 34.…”
Section: Discussionsupporting
confidence: 80%
“…Others have also shown that T RM numbers are increased in livers with chronic HBV infection compared with healthy livers 31. Recent large-scale single-cell RNA-sequencing on T cells from a majority of HBV-related HCCs also found that T REG and exhausted CD8 + T cells (with similar gene signatures as our current study) were enriched in the tumour 32. The important roles of NK cells in HBV infection and HCC have been widely described 33 34.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, CTLA4 and PAK2 mRNA levels were higher in tumor-infiltrating Tregs than in Tregs purified from the surrounding, nontumoral tissues or from the blood, as well as in Teff cells purified from the surrounding tissue, peripheral blood, or even from tumor-infiltrating Teff cell subsets (60). Similar observations were made for PAK2 in breast carcinoma and hepatocellular carcinoma clinical samples (61,62). These data suggest that, in clinical situations, the CTLA4/PKCη/GIT2/PAK2/αPIX pathway plays an important and selective role in the function of intratumoral Tregs.…”
Section: Cd11bsupporting
confidence: 65%
“…As CD4+ T cell subsets are differentiated by their putative functionality, quantifying of transcript expression on the single cell level can be used to identify gene expression programs that underlie those functional divisions. Single cell sequencing of T cells isolated from patients with liver cancer identified 11 distinct CD4 and CD8 T cell populations, some of which were expanded in hepatocellular carcinoma and marked by specific gene signatures [65••]. The functional diversity of natural killer T (NKT) cells is difficult to characterize using cytometry alone; however, single cell RNA-seq analysis revealed differential patterns of gene expression that resolve NKT subsets and indicate potential functions [66].…”
Section: High-dimensional Analyses Reveal An Expanded View Of Cd4+ T mentioning
confidence: 99%